Investigating the role of the built environment, socio-economic status, and lifestyle factors in the prevalence of chronic diseases in Mashhad: PLS-SEM model - Kiyavash Irankhah; Kiyavash Irankhah; Soheil Asadimehr; Behzad Kiani; Jamshid Jamali; Jamshid Jamali; Reza Rezvani; Seyyed Reza Sobhani; Seyyed Reza Sobhani (Frontiers Media S.A., 2024)
BackgroundChronic diseases remain a significant contributor to both mortality and disability in our modern world. Physical inactivity and an unhealthy diet are recognized as significant behavioral risk factors for chronic diseases, which can be influenced by the built environment and socio-economic status (SES). This study aims to investigate the relationship between the built environment, SES, and lifestyle factors with chronic diseases.MethodsThe current study was conducted in Mashhad's Persian cohort, which included employees from Mashhad University of Medical Sciences (MUMS). In the study, 5,357 participants from the cohort were included. To assess the state of the built environment in Mashhad, a Geographic Information System (GIS) map was created for the city and participants in the Persian Mashhad study. Food intake and physical exercise were used to assess lifestyle. A food frequency questionnaire (FFQ) was used to assess food intake. To assess food intake, the diet quality index was computed. To assess the link between variables, the structural model was created in accordance with the study's objectives, and partial least square structural equation modeling (PLS-SEM) was utilized.ResultsThe chronic diseases were positively associated with male sex (p < 0.001), married (p < 0.001), and higher age (p < 0.001). The chronic diseases were negatively associated with larger family size (p < 0.05), higher SES (p < 0.001), and higher diet quality index (DQI) (p < 0.001). No significant relationship was found between chronic disease and physical activity.ConclusionFood intake and socioeconomic status have a direct impact on the prevalence of chronic diseases. It seems that in order to reduce the prevalence of chronic diseases, increasing economic access, reducing the class gap and increasing literacy and awareness should be emphasized, and in the next step, emphasis should be placed on the built environment.